Synthesis of Ru alkylidene complexes - Kadyrov, Renat; Rosiak, Anna (Beilstein Journal of Organic Chemistry, 2011)
The present work describes the robust synthesis of Ru alkylidene complexes (PCy3)2Cl2Ru=CHR – precursors for metathesis catalysts. Moreover, the dynamic behavior of complexes where R = 2-naphthyl and 2-thienyl was studied. 1H NMR techniques were employed to establish the preferred conformations in solution for both complexes and the energy barrier for rotation around single (Ru=)CH–C(thienyl) bond was estimated (ΔG≠303K = 12.6 kcal/mol).
Keywords: alkylidene complexes; metathesis; rotation barrier; ruthenium